THE TOBACCO INSTITUTE'S FIRE SAFETY EDUCATION PROGRAM. (Tufts Archival Research Center, 2007)
Summary of the Tobacco Institute's fire safety program. Calls the objective of the program to be the assistance in fire service and the reduction of accidental fires. Mentions "Fire Care", a program for senior citizens as well as the other activities the tobacco institute is involved with regarding fire safety. Points out that the Tobacco Institute seeks no publicity or compensation for its efforts.